An activated triple bond linker enables ‘click’ attachment of peptides to oligonucleotides on solid support - Wenska, Malgorzata (Oxford University Press, 2011)
A general procedure, based on a new activated alkyne linker, for the preparation of peptide–oligonucleotide conjugates (POCs) on solid support has been developed. With this linker, conjugation is effective at room temperature (RT) in millimolar concentration and submicromolar amounts. This is made possible since the use of a readily attachable activated triple bond linker enhances the Cu(I) catalyzed 1,3-dipolar cycloaddition (‘click’ reaction). The preferred scheme for conjugate preparation involves sequential conjugation to oligonucleotides on solid support of (i) an H-phosphonate-based aminolinker; (ii) the triple bond donor p-(N-propynoylamino)toluic acid (PATA); and (iii) azido-functionalized peptides. The method gives conversion of oligonucleotide to the POC on solid support, and only involves a single purification step after complete assembly. The synthesis is flexible and can be carried out without the need for specific automated synthesizers since it has been designed to utilize commercially available oligonucleotide and peptide derivatives on solid support or in solution. Methodology for the ready conversion of peptides into ‘clickable’ azidopeptides with the possibility of selecting either N-terminus or C-terminus connection also adds to the flexibility and usability of the method. Examples of synthesis of POCs include conjugates of oligonucleotides with peptides known to be membrane penetrating and nuclear localization signals.